A Study on Consumer Behavior towards Fmcg Products among the Rural- Suburban Hhs of Ernakulam - Kumar NA and Joseph J (J Glob Econ, 2014)
The rural consumers are known to earn low income, have low level of literacy, low level of brand awareness, asymmetric information, inadequate communication and transportation facilities. The Rural markets and sub-urban markets are now expanding in Kerala with ever greater penetration index, as the growth seems stunted in the urban markets. In this study, Rural & suburban areas of Ernakulam with a sample size of 100 respondents. The study intends to identify the level of influence of various factors on the purchase of FMCG products-soaps & detergents among the rural/ semi urban consumers. The study emphasized that rural consumers gave more importance to the ‘quality’ of the FMCG-personal care brands they bought rather than the normative influences or social appeal vide celebrity endorsements in the mass media.